PEMETAAN SPASIAL EKONOMI KREATIF BERBASIS DIGITAL ASSET TEMPLATING DI KOTA CIMAHI - Muhammad Fikri Rasyid Mutaqin; Deden Syarifudin; Furi Sari Nurwulandari (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The creative industry, especially in Cimahi City and in general in Indonesia, is developing so rapidly with the existence of a global marketplace which is a place or facility that creators in Cimahi can use. However, when the Covid-19 pandemic hit a lot of business people who lost their livelihoods. There were no previous researchers who discussed Digital Asset-based Creative Economy in Cimahi City from a spatial perspective. This article discusses the solutions that the Cimahi City government through the UPTD Cimahi Technopark to overcome the problems that exist in the City of Cimahi, especially in the field of Creative Economy which can be potential and solutions to existing problems and can become branding that can be used by the City of Cimahi. This study uses qualitative methods using descriptive analysis instruments combined with collaborative planning methods. The results of the study show that there is a Cimahi City program that has the potential to be developed and can become a Cimahi City branding. More than 22 studios have been born from the Cimahi Makerspace Digital Program with a total income of Rp. 1,235,718,618. UPTD Cimahi Technopark is the center of development for Cimahi Makerspace Digital activities. This activity center includes production, marketing, distribution and marketing activities. This activity includes education and training activities in collaboration between the Government, Academics, and business people, as well as communities in Cimahi City who have the same abilities and goals to achieve a successful Cimahi Makerspace Digital program in Cimahi City. This article contributes to the creative economics of the digital creative industry sector which is practically used as a consideration for the government in preparing detailed strategic plans or city master plans.